2021
DOI: 10.1111/jbg.12542
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Copy Number Variations regions in Djallonké sheep

Abstract: A total of 184 Djallonké (West African Dwarf) sheep of Burkina Faso were analysed for Copy Number Variations (CNV) using Ovine 50 K SNP BeadChip genotyping data and two different CNV calling platforms: PennCNV and QuantiSNP. Analyses allowed to identify a total of 63 candidate Copy Number Variations Regions (CNVR) on 11 different ovine chromosomes covering about 82.5 Mb of the sheep genome. Gene‐annotation enrichment analysis allowed to identify a total of 751 potential candidate ovine genes located in the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…The number of CNVs and CNVRs identified in this study was not directly comparable with other previously reported papers due to differences in the used algorithms, technologies, filter criteria, and numbers of tested samples and breeds [ 42 ]. Although the use of SNP arrays is, nowadays, a standard method, they vary in density and number of markers, ranging from 50K [ 2 , 3 , 4 ] to 600K [ 43 , 44 , 45 ]; for example, Ma et al [ 44 ], analyzing 48 Chinese sheep with the 600K SNP array, identified a higher number of CNVRs (1296) with a smaller size (about 96 Kb) compared with ours.…”
Section: Discussioncontrasting
confidence: 77%
“…The number of CNVs and CNVRs identified in this study was not directly comparable with other previously reported papers due to differences in the used algorithms, technologies, filter criteria, and numbers of tested samples and breeds [ 42 ]. Although the use of SNP arrays is, nowadays, a standard method, they vary in density and number of markers, ranging from 50K [ 2 , 3 , 4 ] to 600K [ 43 , 44 , 45 ]; for example, Ma et al [ 44 ], analyzing 48 Chinese sheep with the 600K SNP array, identified a higher number of CNVRs (1296) with a smaller size (about 96 Kb) compared with ours.…”
Section: Discussioncontrasting
confidence: 77%
“…Coelho Ladeira detected 216 CNVRs from 491 Santa Inês individuals using the the 50 K SNP array 13 . Different results across studies may be due to different algorithms used for each study, quality control procidures,numbers of individuals and breed chrachteristics 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past twenty years, a large number of CNVs have been revealed and identi ed by using array comparative genome hybridization (aCGH) chips and high-density SNP chips in domestic animals, such as cattle, sheep, goats, horses, dogs, chickens, turkeys and ducks. Meanwhile, numerous CNV-covered genes have been shown to be associated with coat color, growth, fertility and production [1,2], immune response [3][4][5][6][7], olfactory transduction [8][9][10][11], molecular function [12,13], lipid metabolism [4,9,[14][15][16]] and environmental adaptability [17]. Compared with aCGH and SNP chips, the sensitivity of which is mainly limited by the density of the probes, whole genome resequencing can be used to detect new and rare CNVs.…”
Section: Introductionmentioning
confidence: 99%